2018
DOI: 10.14710/reaktor.18.1.45-50
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microwave Irradiation on Extraction of Chitosan from Shrimp Shell Waste

Abstract: Chitosan is natural polysaccharides which is nontoxic, biodegradable, and biocompatible and have many advantages in various kinds of fields including health, food, agriculture, and industry. Chitosan usually take long time to extract by conventional method for deacetylation process of chitin. Raw material for chitosan can be found in shrimp shell waste. Chitosan manufactures usually need high temperatures and chemicals in large quantities and it takes much time and consumes a lot of energy where will give bad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Recently, microwave irradiation has been shown to be a promising technique for the extraction and modification of polysaccharides from natural sources [ 61 ], including chitin chemistry. This method is mostly used as an alternative for the preparation of chitosan from various chitinous sources [ 62 , 63 , 64 , 65 ]. It has been confirmed that microwave-assisted chitin processing reduces the time of deacetylation from ∼8 h [ 64 ] to 5.5 min [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, microwave irradiation has been shown to be a promising technique for the extraction and modification of polysaccharides from natural sources [ 61 ], including chitin chemistry. This method is mostly used as an alternative for the preparation of chitosan from various chitinous sources [ 62 , 63 , 64 , 65 ]. It has been confirmed that microwave-assisted chitin processing reduces the time of deacetylation from ∼8 h [ 64 ] to 5.5 min [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other emerging extraction techniques include the use of ionic liquids, deep eutectic solvents (DES), microwave, ultrasound, and pulsed electric field technologies for the deproteinization [ 142 ]. Of these approaches, microwave-assisted extraction, ionic liquids, deep eutectic solvents and ultrasound-assisted extraction [ 133 , 145 ] offers enhanced process control, energy-efficiency, and cost-effectiveness [ 130 , 141 ] in comparison with the conventional chemical approaches. Especially the use of emerging green solvents (ionic liquids and deep eutectic solvents (DESs)) have been applied to many fields, such as biomass for separation and purification, pretreatment and synthesis of polymers including chitin extraction.…”
Section: Chitin Extraction Techniquesmentioning
confidence: 99%